A yarn and a fabric
Patent Information
- Application Number
- CN202510525923.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
虽然该纱线的蓬松度达到90%以上,但由于纱线里含有高收缩短纤维,受热收缩后会导致纱线很难被拉伸,纱线弹性不足
[0014]本发明的纱线中含有可溶出纤维和具有潜在卷缩性的双组分复合短纤维,利用该纱线纺织并减量去除可溶出纤维后,得到的面料具有良好的弹性和蓬松度,因此本发明的纱线可广泛用于机织、针织等各种面料。
Smart Images

Figure BDA0005375643510000111
Abstract
Description
Technical Field
[0001] This invention belongs to the field of textile technology and relates to a yarn and a fabric spun from it. Background Technology
[0002] With market development and the continuous improvement of living standards, people have higher and higher requirements for clothing, requiring fabrics to have both elasticity and fluffiness.
[0003] Chinese patent CN102454004A discloses a composite elastic filament core-spun yarn fabric and its preparation method. The fabric uses PTT / PET parallel composite elastic filaments as the core yarn, wrapped with natural fibers and / or chemical fibers. After wet heat treatment, the PTT / PET composite single fibers form high crimp, thus possessing elasticity. Although the yarn has good elasticity, its bulkiness is insufficient due to the constraint of the outer fibers.
[0004] Chinese patent CN104651996A discloses a bulky blended yarn and its production method. The yarn is obtained by dissolving and removing water-soluble polyvinyl alcohol fibers, and is a short-fiber yarn with a core-sheath structure formed from at least high-shrinkage fibers and ordinary short fibers. Although the yarn has a bulkiness of over 90%, the presence of high-shrinkage fibers makes it difficult to stretch after heat shrinkage, resulting in insufficient elasticity. Summary of the Invention
[0005] The purpose of this invention is to provide a yarn containing soluble fibers and bicomponent composite short fibers with potential shrinkage, and a fabric made from the yarn that has high elasticity and high bulkiness.
[0006] The technical solution of this invention is:
[0007] A yarn containing soluble fibers and potentially shrinkable bicomponent composite short fibers, wherein the soluble fibers account for 10-40 wt% of the yarn and the potentially shrinkable bicomponent composite short fibers account for 60-90 wt% of the yarn.
[0008] Preferably, the bicomponent composite short fiber is a parallel composite short fiber or an eccentric core-sheath composite short fiber.
[0009] Preferably, the shrinkage rate of the bicomponent composite short fiber after hot water treatment at 130°C is 30-60%.
[0010] Preferably, the soluble fiber is a high-shrinkage soluble filament.
[0011] Preferably, the boiling water shrinkage rate of the high-shrinkage soluble filament is 20-50% higher than that of the bicomponent composite short fiber.
[0012] The present invention also discloses a fabric comprising short-fiber yarn obtained by reducing the amount of soluble fibers removed from the above-mentioned yarn.
[0013] Preferably, the short-fiber yarn, after being treated with hot water at 130℃, has an elongation at which it has a stretch rate of 15-60%, an elasticity at which it has a stretch rate of 85-95%, and a bulkiness of 3.0-4.5cm. 3 / g.
[0014] The yarn of the present invention contains soluble fibers and bicomponent composite short fibers with potential shrinkage. After weaving with this yarn and removing the soluble fibers by weight reduction, the resulting fabric has good elasticity and bulkiness. Therefore, the yarn of the present invention can be widely used in various fabrics such as woven and knitted fabrics. Detailed Implementation
[0015] The yarn of this invention contains soluble fibers and bicomponent composite short fibers with potential shrinkage. These bicomponent composite short fibers exhibit potential shrinkage and, after heat treatment, form a three-dimensional helical crimp structure. The bicomponent composite short fibers and soluble fibers are intertwined in the yarn. After the soluble fibers dissolve, the bicomponent composite short fibers in the yarn are relatively loose, which facilitates full crimping of the bicomponent composite short fibers after heating, resulting in fabrics with better elasticity and bulkiness.
[0016] To achieve good elasticity and bulkiness in the fabric, this invention limits the content of soluble fibers in the yarn to 10-40 wt%. If the content of soluble fibers is less than 10 wt%, the space freed up after the soluble fibers dissolve is too small, and the curling structure of the potentially shrinkable bicomponent composite short fibers after heating is restricted by space, resulting in poor fabric elasticity and low bulkiness. If the content of soluble fibers is greater than 40 wt%, although a larger space can be obtained after dissolving, and the curling structure of the potentially shrinkable bicomponent composite short fibers after heating is not restricted, the amount of potentially shrinkable bicomponent composite short fibers producing a curled structure is relatively small when the yarn fineness is uniform, resulting in poor overall elasticity; moreover, because the gaps between the potentially shrinkable bicomponent composite short fibers become larger, the bulkiness decreases after compression and is difficult to recover. To achieve even better elasticity and bulkiness in the fabric, this invention preferably specifies that the soluble fibers in the yarn account for 20-30 wt%.
[0017] The present invention also specifies that the bicomponent composite short fibers with potential shrinkage account for 60-90 wt% of the yarn, preferably 70-80 wt%, and the short fiber yarn and the final fabric after leaching and removing the soluble fibers have good elasticity and high bulkiness.
[0018] In addition to the aforementioned soluble fibers and bicomponent composite short fibers with potential shrinkage, the yarn may also contain short fibers such as cotton, polyester, and acrylic, without affecting the elasticity and bulkiness of the short fiber yarn and the final fabric after the leaching treatment.
[0019] Potentially crimped fibers refer to fibers that can form a three-dimensional spiral crimp structure when heated. This invention does not impose particular restrictions on the specific composite form of the bicomponent composite short fibers with potential crimp, as long as they possess potential crimp, they can be side-by-side composite short fibers, eccentric core-sheath composite short fibers, island-type composite short fibers, or multi-layered composite short fibers. Considering that compared with other forms of composite short fibers, the distance between the centers of gravity of the two components in side-by-side composite short fibers is large, resulting in good fiber crimp and thus imparting good crimp and elasticity to the yarn, this invention preferably uses side-by-side composite short fibers as the composite form of the bicomponent composite short fibers with potential crimp.
[0020] The present invention does not specifically limit the components of the bicomponent composite short fiber with potential shrinkage. Examples include composite fibers of polyethylene terephthalate and propylene terephthalate (PTT / PET), composite fibers of high-shrinkage polyethylene terephthalate and ordinary polyethylene terephthalate (high-shrinkage PET / ordinary PET), composite fibers of high-shrinkage polyamide and ordinary polyamide (high-shrinkage PA / ordinary PA), and composite fibers of high-shrinkage acrylic fiber and low-shrinkage acrylic fiber (high-shrinkage PAN / low-shrinkage PAN).
[0021] The cross-section of the potentially shrinkable bicomponent composite short fiber can be circular, or it can be triangular, elliptical, flat, or other irregular shapes. Considering that a circular cross-section can distribute stress more evenly when subjected to external forces, thus exhibiting higher strength and better toughness, the fiber is less prone to breakage, and it shows good stability during spinning and use, the present invention preferably uses a circular cross-section.
[0022] Preferably, the shrinkage rate (hereinafter referred to as hot water shrinkage rate) of the potentially shrinkable bicomponent composite short fibers after hot water treatment at 130°C is 30-60%. If the hot water shrinkage rate is too small, the potentially shrinkable bicomponent composite short fibers will produce less curl after heating, and the elasticity and bulkiness of the fabric will tend to deteriorate. If the hot water shrinkage rate is too large, after the removal of soluble fibers, the shrinkage of the potentially shrinkable bicomponent composite short fibers on the surface of the short fiber yarn will lead to a reduction in the curling space of the potentially shrinkable bicomponent composite short fibers in the inner layer of the short fiber yarn, and the elasticity and bulkiness of the fabric will also tend to deteriorate. To obtain better elasticity and bulkiness of the fabric, the hot water shrinkage rate of the potentially shrinkable bicomponent composite short fibers is more preferably 40-50%.
[0023] This invention does not specifically limit the composition of the soluble fiber, which can be polyvinyl alcohol fiber, polyamide fiber, or polyester fiber. Depending on the dissolution mechanism, it can be a water-soluble polymer fiber or an alkali-soluble polymer fiber. Its form can be short fiber or filament. The filament can be fully drawn yarn (FDY) or false-twist yarn (DTY).
[0024] To further improve the elasticity and bulk of the fabric, the soluble fiber is preferably a high-shrinkage soluble filament. Before soluble fiber is dissolved, the yarn can be treated with boiling water to cause the high-shrinkage soluble filament to shrink, while the potentially shrinkable bicomponent composite staple fiber does not shrink or only shrinks slightly. Due to the shrinkage of the high-shrinkage soluble filament, the potentially shrinkable bicomponent composite staple fiber arches in the yarn. Then, the staple fiber yarn after the high-shrinkage soluble filament has been dissolved is treated with hot water at 130°C to make the arched potentially shrinkable bicomponent composite staple fiber curl to a greater extent, thereby obtaining a fabric with greater elasticity and bulk.
[0025] High-shrinkage fibers (functional fibers with potential heat shrinkage properties) are fibers with a relatively high shrinkage rate compared to conventional fibers. Conventional fibers typically have a maximum boiling water shrinkage rate of no more than 10% after being heated, while high-shrinkage fibers generally have a boiling water shrinkage rate of over 20%, and can even reach 60% to 70%.
[0026] Understandably, the greater the arching of the potentially shrinkable bicomponent composite short fibers after boiling water treatment, the greater the crimp after 130°C hot water treatment, resulting in better elasticity and bulkiness of the fabric. It's important to note that if the arching of the potentially shrinkable bicomponent composite short fibers after boiling water treatment is too great, the cohesion between the potentially shrinkable bicomponent composite short fibers will be insufficient after the high-shrinkage soluble filament is further treated at 130°C. When stretched, the potentially shrinkable bicomponent composite short fibers are prone to dispersion and difficulty in recovery, leading to a lower recovery rate and reduced elasticity in the short fiber yarn. In this invention, the arching degree of the potentially shrinkable bicomponent composite short fibers after boiling water treatment is controlled by adjusting the difference in boiling water shrinkage rates between the high-shrinkage soluble filament and the potentially shrinkable bicomponent composite short fibers. The greater the difference, the greater the arching degree. For the reasons mentioned above, the boiling water shrinkage rate of the preferred high-shrinkage soluble filament is 20-50% higher than that of the bicomponent composite short fiber with potential crimping.
[0027] It should be noted that, based on different testing methods, the boiling water shrinkage rate of the high-shrinkage soluble filament refers to the boiling water shrinkage rate of a bundle of filaments, while the boiling water shrinkage rate of the bicomponent composite short fiber refers to the boiling water shrinkage rate of a single short fiber.
[0028] In this invention, the high-shrinkage soluble filament is preferably a high-shrinkage soluble polyester filament, which has a high heat shrinkage rate and shrinks significantly after heating; the dissolution conditions are simple and controllable, and it can be completely dissolved without gelation problems; after dissolution under alkaline conditions, it is easy to recycle or treat, and has good environmental performance.
[0029] In this invention, when the soluble fiber is a short fiber, it can be mixed with bicomponent composite short fibers during the carding or drawing stage, and then twisted on a spinning machine (ring spinning, Siro spinning, etc.) to obtain yarn; when the soluble fiber is a filament, the bicomponent composite short fibers with potential crimping can first be made into short fiber bundles, and then compounded and twisted with the soluble fiber on a spinning machine (core spinning) to obtain yarn.
[0030] By spinning the yarn of the present invention and then removing soluble fibers through weight reduction, a fabric with both high elasticity and high bulk can be obtained. The fabric can be spun alone from the yarn of the present invention, or it can be spun together with other yarns. When spun together with other yarns, the amount of the yarn of the present invention is preferably 70 wt% or more to obtain a fabric with superior elasticity and bulk. The present invention does not particularly limit the other yarns; they can be selected as needed. Examples include 100% pure cotton yarn, 100% pure polyester yarn, 100% pure viscose yarn, 100% pure acrylic yarn, and polyester-cotton blended yarn.
[0031] The final fabric contains short-staple yarns made by reducing the amount of soluble fibers removed from the aforementioned yarns. Preferably, the short-staple yarns, after being treated with hot water at 130°C, have an elongation at break of 15-60%, an elasticity at break of 85-95%, and a bulkiness of 3.0-4.5 cm. 3 / g. The greater the elongation at break, the better the stretchability of the staple fiber yarn; the greater the elasticity at break, the better the resilience of the staple fiber yarn; the greater the bulkiness, the more pronounced the expansion and softness of the staple fiber yarn. In this invention, the elasticity of the staple fiber yarn is characterized by a combination of elongation at break and elasticity at break. When the elasticity at break is above 85%, the greater the elongation at break, the greater the elasticity of the staple fiber yarn; when the elasticity at break is less than 85%, it is difficult to recover after stretching, and the elasticity of the staple fiber yarn is poor.
[0032] In addition, without damaging the fabric, the feel and appearance of the fabric can be improved through physical and / or chemical methods, such as stiffening, softening or napping; the quality of the fabric can also be improved and new functions can be given to the fabric through anti-wrinkle, stain-resistant, moth-proof or antibacterial treatments.
[0033] This invention produces a yarn by spinning a bicomponent composite short fiber containing soluble fibers and potentially shrinkable fibers. The fabric obtained by weaving this yarn and then removing the soluble fibers through weight reduction exhibits excellent properties of high elasticity and good bulkiness.
[0034] The present invention will be further described below with reference to embodiments and comparative examples, but the present invention is not limited thereto. The various physical property parameters involved in the present invention were tested according to the following methods.
[0035] (1) Content of soluble fibers in yarn
[0036] Select a 300mm yarn as a sample and weigh it (Ga). First, soak the sample yarn in 90℃ hot water for 30 minutes, then remove the yarn and wash it under running water. Next, soak the yarn in 90℃ hot alkaline water (10% NaOH solution) for 30 minutes, then remove the yarn and wash it under running water. Dry the yarn in an 80℃ oven for 30 minutes and weigh the dried yarn (Gb). The weight percentage of soluble fibers in the yarn is [(Ga-Gb) / Ga]×100%. Take four more yarns and repeat the above steps for testing. The final result is the average of five tests.
[0037] (2) Content of bicomponent composite short fibers in yarn
[0038] A 300mm yarn was selected as a sample yarn and weighed (Gd). The twist meter was set to a 200mm interval, and the yarn sample was untwisted using the direct counting method. The untwisted portion of the yarn was cut, and short fibers were separated using tweezers. Short fibers with a three-dimensional helical structure were selected under a KEYENCE VH-ZST digital microscope (lens adjusted to ZS20, magnification 100x). One of these short fibers was selected, and a cross-section sample was taken using the copper plate method. The cross-section was observed to be bicomponent under a KEYENCE VH-ZST digital microscope (lens adjusted to ZS200, magnification 2000x), indicating that it was a bicomponent composite short fiber. The weight (Gc) of all bicomponent composite short fibers was measured. The weight percentage of the bicomponent composite short fibers in the yarn was [(Gc×3) / (Gd×2)]×100%. The remaining four dissolved yarn samples were tested using the same method, and the final result was the average of the five tests.
[0039] (3) Hot water shrinkage rate of bicomponent composite short fiber
[0040] Take one bicomponent composite short fiber selected by test method (2) as the test fiber. Place the fiber on the center line of the waterproof sample paper frame and stick it firmly with adhesive. Wait for 20 minutes. Cut off the two sides of the waterproof sample paper frame parallel to the fiber axis. Along the fiber axis, use the clamp on the YG362B crimp elasticity tester to pinch the waterproof sample paper at one end of the sample. Clamp the other end of the waterproof sample paper to the lower clamp of the crimp elasticity tester and apply a tension of 5.88 mN / tex. The equipment automatically measures the length of the short fiber (L1). Remove the sample and place it in a special gauze for heat treatment (130℃ hot water × 30 min). Then take out the fiber and put it into a dryer for drying treatment (90℃ × 20 min). Then take out the fiber and put it back into the crimp elasticity tester. Apply a tension of 5.88 mN / tex to measure the length (L2). The shrinkage rate of the fiber in 130℃ hot water is [(L1-L2) / L1] × 100%. Nine more bicomponent composite short fibers were selected, and their hot water shrinkage rates were measured using the same method described above. The average of these ten hot water shrinkage rates was taken as the 130℃ hot water shrinkage rate of the bicomponent composite short fiber.
[0041] (4) Boiling water shrinkage rate
[0042] Take one yarn as a sample yarn. After untwisting the sample yarn using the direct counting method on a twist meter, separate the short fibers and the soluble filaments. Clamp one end of the filament with a clip and suspend it on a manual length measuring frame. Apply a tension of 0.1 g / D for 30 seconds below the other end, and then mark two points on the filament with a waterproof marker, 500 mm apart. Remove the filament and place it in a mesh bag in a relaxed state. Place the mesh bag in boiling water (100℃) for 30 minutes. Remove the mesh bag and take out the yarn. Use absorbent paper to absorb the water. After it is fully dried, suspend the sample on the manual length measuring frame and apply a tension of 0.1 g / D for 30 seconds. The length L3 between the two marks is the length of the filament after shrinkage. The boiling water shrinkage rate of this filament is [(500-L3) / 500]×100%. Nine more yarns were taken out and the boiling water shrinkage rate of the soluble filaments was separated and tested using the same method as described above. The final result was the average of 10 tests.
[0043] Referring to test method (3), the heat treatment conditions were changed to boiling water for 20 minutes, while the rest remained unchanged. The boiling water shrinkage rate of the bicomponent composite short fiber was tested, and the final result was the average of 10 tests.
[0044] (5) Elongation and elasticity of staple fiber yarn
[0045] Short fiber yarns were removed from the fabric, and their elongation and elasticity were tested according to JIS L 1013:2021 8.11A method.
[0046] (6) Loft of staple fiber yarn
[0047] Twenty short-fiber yarns were removed from the fabric. Using a 30cm cutting table, a tension of 0.5cN / tex was applied, and each of the 20 yarns was cut into 30cm lengths. Ten of these 30cm yarn samples (Sample 1) were used to test the short-fiber yarn linear density, and the other ten 30cm yarn samples (Sample 2) were used to test the apparent diameter of the short-fiber yarn. Sample 1 was weighed (Gh, in g), and the weight (in g) of 1cm of yarn was calculated as Gh / 300. For Sample 2, one end of the yarn was glued to a black cardboard, and a tension of 0.5cN / tex was applied to the other end. Glue was applied near the edge of the cardboard to fix the yarn in place. Using a KEYENCE VH-ZST digital microscope with the lens set to ZS20 and magnification 50x, three points were randomly selected on each yarn to measure its diameter. The average of the 30 measurements was taken as the apparent diameter of the short-fiber yarn, denoted as D (in cm). The bulkiness of staple fiber yarn is (300×π×D) 2 ) / (4×Gh).
[0048] Example 1
[0049] Bicomponent composite short fibers (high-shrinkage PET / low-shrinkage PET, side-by-side, boiling water shrinkage 0.5%, hot water shrinkage 40.0% at 130℃) with potential crimping properties and a single filament fineness of 2.2 dtex are selected. The fibers are then processed sequentially through opening and cleaning, carding, drawing (two draws, draft ratio 8, basis weight 20g / 5m), and roving (draft ratio 8, twist coefficient 0.6, basis weight 5.0g / 10m) to obtain roving. High-shrinkage soluble polyester filaments (boiling water shrinkage 40.5%) of 56 dtex are selected as the soluble fiber. The roving and soluble fiber are combined through core-spun yarn at a weight ratio of 70:30 (i.e., the soluble fiber accounts for 30 wt% of the yarn). Core-spun spinning process: rotation speed 12000r / min, draft ratio 42.3 times, twist coefficient 3.7, filament tension 7.5g, to obtain the 32-count long-short composite yarn of the present invention.
[0050] Using the aforementioned composite yarns of varying lengths, a plain weave with a warp density of 68 threads / inch and a weft density of 62 threads / inch was used to weave the grey fabric. The grey fabric then underwent a series of treatments: pre-bleaching (90℃×20 minutes), alkali reduction (NaOH solid, 95℃×30 minutes), pre-shrinking (130℃×30 minutes), intermediate setting (180℃×1 minute), dyeing (130℃×30 minutes), and final setting (170℃×1 minute) to obtain the final fabric. The results of various performance tests are shown in Table 1.
[0051] Example 2
[0052] High-shrinkage soluble polyester filament with a total fineness of 33 dtex (boiling water shrinkage rate of 40.5%) was selected as the soluble fiber. The proportion of soluble fiber in the yarn was adjusted to 10 wt%. The core-spun process was carried out with the following parameters: rotation speed 12000 r / min, draft ratio 18.3, twist coefficient 3.7, and filament tension 4.5 g. The rest of the process was the same as in Example 1, resulting in an 18-count composite yarn and fabric. The test results for various properties are shown in Table 1.
[0053] Example 3
[0054] High-shrinkage soluble polyester filament with a total fineness of 75 dtex (boiling water shrinkage rate of 40.5%) was selected as the soluble fiber. The proportion of soluble fiber in the yarn was adjusted to 40 wt%. The core-spun process was carried out with the following parameters: rotation speed 12000 r / min, draft ratio 48.4, twist coefficient 3.7, and filament tension 10.0 g. The rest of the process was the same as in Example 1, resulting in a 32-count composite yarn and fabric. The test results for various properties are shown in Table 1.
[0055] Example 4
[0056] A bicomponent composite short fiber (high-shrinkage PET / low-shrinkage PET, eccentric core-sheath type, boiling water shrinkage rate of 0.5%, hot water shrinkage rate of 40.0% at 130℃) with a single filament fineness of 2.2dtex and an average length of 38mm and potential shrinkage was selected for spinning. The rest was the same as in Example 1. A 32-count long-short composite yarn and fabric were obtained. The results of various performance tests are shown in Table 1.
[0057] Example 5
[0058] A bicomponent composite short fiber (high-shrinkage PET / low-shrinkage PET, side-by-side, with a boiling water shrinkage rate of 0.5% and a hot water shrinkage rate of 30.0% at 130℃) with a single filament fineness of 2.2dtex and an average length of 38mm and potential shrinkage properties was selected for spinning. The rest was the same as in Example 1. A 32-count long-short composite yarn and fabric were obtained. The test results of various properties are shown in Table 1.
[0059] Example 6
[0060] A bicomponent composite short fiber (high-shrinkage PET / low-shrinkage PET, side-by-side, with a single filament fineness of 2.2 dtex and an average length of 38 mm and potential for crimping, was selected for spinning. The rest was the same as in Example 1, and a 32-count long-short composite yarn and fabric were obtained. The results of various performance tests are shown in Table 1.
[0061] Example 7
[0062] A bicomponent composite short fiber (high-shrinkage PET / low-shrinkage PET, side-by-side, with a boiling water shrinkage rate of 0.5% and a hot water shrinkage rate of 10.0% at 130℃) with a single filament fineness of 2.2dtex and an average length of 38mm and potential shrinkage was selected for spinning. The rest was the same as in Example 1. A 32-count long-short composite yarn and fabric were obtained. The test results of various properties are shown in Table 1.
[0063] Example 8
[0064] A bicomponent composite short fiber (high-shrinkage PET / low-shrinkage PET, side-by-side, with a single filament fineness of 2.2 dtex and an average length of 38 mm and potential shrinkage) with potential shrinkage was selected for spinning. The rest was the same as in Example 1. A 32-count long-short composite yarn and fabric were obtained. The results of various performance tests are shown in Table 1.
[0065] Example 9
[0066] Water-soluble polyvinyl alcohol (PVA) short fibers with a fineness of 1.67 dtex and an average length of 38 mm were selected as the soluble fibers, and ring spinning was performed. The ring spinning process was as follows: rotation speed 12000 r / min, draft ratio 29.4, twist coefficient 3.7, and the rest were the same as in Example 1, to obtain a 32-count blended yarn.
[0067] The mixed yarn prepared above was used to weave a plain weave with a warp density of 68 threads / inch × a weft density of 62 threads / inch to obtain a grey fabric. Then, the fabric underwent a pre-treatment process of boiling and bleaching (90℃×20 minutes, PVA leaching) → pre-shrinking (130℃×30 minutes) → intermediate setting (180℃×1 minute) → dyeing (130℃×30 minutes) → setting (170℃×1 minute) to obtain the fabric. The results of various performance tests are shown in Table 1.
[0068] Example 10
[0069] High-shrinkage soluble polyester filament of 56dtex (boiling water shrinkage rate of 20.5%) was selected as the soluble fiber, and the rest was the same as in Example 1, to obtain 32-count long and short composite yarn and fabric. The test results of various properties are shown in Table 1.
[0070] Example 11
[0071] A 56dtex high-shrinkage soluble polyester filament (boiling water shrinkage rate of 50.5%) was selected as the soluble fiber, and the rest was the same as in Example 1, to obtain a 32-count long-short composite yarn fabric. The test results of various properties are shown in Table 1.
[0072] Example 12
[0073] 56dtex non-high shrinkage soluble polyester filament (boiling water shrinkage rate 10.5%) was selected as the soluble fiber, and the rest was the same as in Example 1, to obtain 32-count long and short composite yarn and fabric. The test results of various properties are shown in Table 1.
[0074] Example 13
[0075] High-shrinkage soluble polyester filament with a boiling water shrinkage rate of 60.5% was selected as the soluble fiber, and the rest was the same as in Example 1. 32-count long-short composite yarn and fabric were obtained, and the test results of various properties are shown in Table 1.
[0076] Example 14
[0077] A bicomponent composite staple fiber (high-shrinkage PET / low-shrinkage PET, side-by-side, boiling water shrinkage rate 0.5%, hot water shrinkage rate 40.0% at 130℃) with potential crimping properties, with a single filament fineness of 2.2 dtex and an average length of 38 mm, was mixed with cotton fiber (boiling water shrinkage rate 0.8%) at a weight ratio of 6:1. The mixture was then sequentially processed through opening and cleaning, carding, and drawing (3 times drawing, draft ratio 8 times, basis weight 20 g / 5m) to obtain roving. The remaining steps were the same as in Example 1, resulting in a 32-count composite yarn and fabric. The performance test results are shown in Table 1.
[0078] Comparative Example 1
[0079] High-shrinkage soluble polyester filament of 25 dtex (boiling water shrinkage rate of 40.5%) was selected as the soluble fiber, and the proportion of soluble fiber in the yarn was adjusted to 5 wt%. Core-spun process: rotation speed 12000 r / min, draft ratio 11.4 times, twist coefficient 3.7, filament tension 3.4 g, the rest is the same as in Example 1, to obtain 12-count long and short composite yarn and fabric, and the test results of various properties are shown in Table 1.
[0080] Because the proportion of soluble fibers in the yarn is relatively small, the crimping of the bicomponent composite short fibers is limited by space, resulting in lower elasticity and bulkiness of the final fabric.
[0081] Comparative Example 2
[0082] 75 dtex high-shrinkage soluble polyester filament (boiling water shrinkage rate 40.5%) was selected as the soluble fiber, and the proportion of soluble fiber in the yarn was adjusted to 50 wt%. Core-spun process: rotation speed 12000 r / min, draft ratio 68.2 times, twist coefficient 3.7, filament tension 10.0 g. The rest was the same as in Example 1, resulting in a 40-count composite yarn and fabric. The performance test results are shown in Table 1.
[0083] Because the yarn contains a high proportion of soluble fibers and a low proportion of bicomponent composite short fibers, the final fabric has low elasticity and bulkiness.
[0084] Comparative Example 3
[0085] 56dtex, insoluble ordinary DTY polyester filament (boiling water shrinkage rate 8.5%) was used to replace the soluble fiber, and the rest was the same as in Example 1, to obtain a 32-count long-short composite yarn.
[0086] The composite yarns of the above-mentioned lengths were used to weave a plain weave with a warp density of 68 threads / inch × a weft density of 62 threads / inch to obtain a grey fabric. Then, the fabric underwent a pre-treatment process of boiling and bleaching (90℃×20 minutes) → pre-shrinking (130℃×30 minutes) → intermediate setting (180℃×1 minute) → dyeing (130℃×30 minutes) → setting (170℃×1 minute) to obtain the fabric. The results of various performance tests are shown in Table 1.
[0087] Because the yarn does not contain soluble fibers, the crimping of the bicomponent composite short fibers is spatially restricted, resulting in lower elasticity and bulkiness of the final fabric.
[0088] Comparative Example 4
[0089] Polyester staple fiber (single-component round, boiling water shrinkage rate 0.5%, hot water shrinkage rate 5.0% at 130℃) with a single filament fineness of 1.35dtex and an average length of 38mm was selected to replace the bicomponent composite staple fiber. The rest was the same as in Example 1. 32-count composite yarn and fabric were obtained. The test results of various properties are shown in Table 1.
[0090] Because short fibers do not curl, the final fabric has lower elasticity and bulkiness.
[0091]
Claims
1. A yarn characterized by: The yarn contains soluble fibers and bicomponent composite short fibers with potential shrinkage, wherein the soluble fibers account for 10-40 wt% of the yarn and the bicomponent composite short fibers with potential shrinkage account for 60-90 wt% of the yarn.
2. The yarn according to claim 1, characterized in that: The bicomponent composite short fiber is either a side-by-side composite short fiber or an eccentric core-sheath composite short fiber.
3. The yarn according to claim 1 or 2, characterized in that: The shrinkage rate of the bicomponent composite short fiber after hot water treatment at 130℃ is 30-60%.
4. The yarn according to claim 1, characterized in that: The soluble fiber is a high-shrinkage soluble filament.
5. The yarn according to claim 4, characterized in that: The boiling water shrinkage rate of the high-shrinkage soluble filament is 20-50% higher than that of the bicomponent composite short fiber.
6. A fabric characterized by: It contains short-fiber yarn made from the yarn of claim 1 after the removal of soluble fibers through weight reduction.
7. The fabric according to claim 6, characterized in that: The short-fiber yarn, after being treated with hot water at 130℃, has an elongation rate of 15-60%, an elasticity rate of 85-95%, and a bulkiness of 3.0-4.5cm. 3 / g.
Citation Information
Patent Citations
Composite elastic filament core-spun yarn fabric and preparation method thereof
CN102454004A
Bulk blended yarn and production method thereof
CN104651996A
